Enhancing the Effectiveness of Educational Supervision: An Analysis of Challenges and Solutions - Eni Veronika Eni Veronika; Marinu Waruwu; Halida Halida; Nuriaini Asriati (Sustainable, 2024)
Obstacles, solutions, and follow-up actions in implementing academic supervision are essential to evaluate the success of the program. Follow-up activities can include providing feedback to teachers to discuss findings from the supervision process. Effective follow-up ensures that the results of academic supervision contribute significantly to enhancing teacher professionalism. This study aims to explore: 1) The obstacles encountered during academic supervision in schools. 2) The follow-up actions taken by principals after conducting academic supervision for teachers. 3) The outcomes of these follow-up actions on teacher performance. 4) This research employs a qualitative approach, focusing on descriptive data to analyze the forms, processes, and results of follow-up activities following academic supervision in schools. The findings reveal that academic supervision and the subsequent coaching activities carried out by school principals play a crucial role in improving teacher performance through effective follow-up.